Surgical procedure of intratympanic injection and inner ear pharmacokinetics simulation in domestic pigs - Moatti, Adele; Connard, Shannon; De Britto, Novietta; Dunn, William A.; Rastogi, Srishti; Rai, Mani; Schnabel, Lauren V.; Ligler, Frances S.; Hutson, Kendall A.; Fitzpatrick, Douglas C.; Salt, Alec; Zdanski, Carlton J.; et al. (Frontiers in Pharmacology, 2024)
One major obstacle in validating drugs for the treatment or prevention of hearing loss is the limited data available on the distribution and concentration of drugs in the human inner ear. Although small animal models offer some insights into the inner ear pharmacokinetics, their smaller organ size and different barrier permeabilities (round window membrane) compared to humans can complicate study interpretation. Developing a reliable large animal model for inner ear drug delivery is crucial for evaluating its potential therapeutic value. The inner and middle ear anatomy of domestic pigs closely resembles that of humans, making them promising candidates for studying inner ear pharmacokinetics. However, challenges arise due to the complex anatomical orientation of their narrow and tortuous external ear canal, frustrating local drug delivery to the inner ear. In this study, we developed a surgical technique to access the tympanic membrane of pigs, successfully delivering dexamethasone and dexamethasone sodium phosphate to the inner ear. Auditory brainstem responses to click and pure tones were measured in pigs before and after drug delivery, revealing no adverse effects on hearing thresholds attributable to the surgery. Additionally, we performed 3D segmentation of the porcine inner ear and used this data to simulate the diffusion of dexamethasone within the inner ear through fluid simulation software (FluidSim). The reported diffusion time and drug concentrations closely mirrored the limited data obtained in humans. In summary, the results demonstrate a technique for conducting inner ear pharmacokinetic studies in pigs and offer a pathway to simulate drug distribution within the human inner ear.